Understanding the increase in opioid overdoses in New Hampshire: A rapid epidemiologic assessment. (1st April 2020) - Meier, Andrea; Moore, Sarah K.; Saunders, Elizabeth C.; McLeman, Bethany; Metcalf, Stephen A.; Auty, Samantha; Walsh, Olivia; Marsch, Lisa A.
Highlights: Respondents reported high availability of fentanyl in New Hampshire (NH). Consensus that fentanyl is the presumptive primary cause of overdose death in NH. Majority of interviewees had knowingly used fentanyl. Confluence of social, structural, and individual factors were associated with use. Lack of prevention, treatment and harm reduction resources were emphasized. Abstract: Background: New Hampshire (NH) has had among the highest rates of fentanyl-related overdose deaths per capita in the United States for several years in a row—more than three times the national average in 2016. This mixed-methods study investigated drug-using practices and perspectives of NH residents who use opioids to inform policy in tackling the overdose crisis. Methods: Seventy-six participants from six NH counties completed demographic surveys and semi-structured interviews focused on drug-using practices and perspectives, including use precursors, fentanyl-seeking behaviors, and experiences with overdose. Rigorous qualitative methods were used to analyze interview data including transcription, coding and content analysis. Descriptive statistics were calculated on quantitative survey data. Results: Eighty-four percent of interviewees had knowingly used fentanyl in their lifetime, 70 % reported overdosing at least once, and 42 % had sought a batch of drugs known to have caused an overdose. The majority stated most heroin available in NH was laced with fentanyl and acknowledged that variability across batches increased overdose risk. Participants reported high availability of fentanyl and limited access to prevention, treatment, and harm reduction programs. There was widespread support for expanding education campaigns for youth, increasing treatment availability, and implementing needle exchange programs. Conclusions: A confluence of factors contribute to the NH opioid overdose crisis. Despite consensus that fentanyl is the primary cause of overdoses, individuals continue to use it and affirm limited availability of resources to address the problem. Policies targeting innovative prevention, harm reduction, and treatment efforts are needed to more effectively address the crisis.